ANALISIS IMPLEMENTASI KEBIJAKAN PEMUNGUTAN RETRIBUSI RUMAH POTONG HEWAN DI KABUPATEN PARIGI MOUTONG - Hildawaty, Jumaria (Katalogis, 2014)
The objectives of the research were to find out and describe Analysis of PolicyImplementation on Butcher House Retribution Collectting in Parigi Moutong Regency .The researcher employed theory of Edward III coverring factors such as Communication, Resources, Disposition and Bureaucratic Structure. This research employed qualitative descriptive methodology. Based on the observation results in the field, the researcher concluded that butcher house in Parigi Moutong Regency have not run well and not totally effective. It was seen from four aspects observed, the aspect of communication, resources and disposition have not supported because they have not become priority program in supporting Rrgional Real Income.